The US Nuclear Policy in the XXI Century: Continuity and Change in the Strategies of the George W. Bush, Barack Obama, and Donald Trump Administrations - E. P. Buzhinsky; V. A. Veselov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
The nuclear policy of the three successive U.S. administrations over the last twenty years has revealed both continuity and change. However, a growing uncertainty over the future of the Treaty between the United States of America and the Russian Federation on Measures for the Further Reduction and Limitation of Strategic Offensive Arms (New START) after February of 2021 necessitates a broader chronological perspective on the evolution of the U.S. nuclear policy in order to separate short-term considerations from long-term trends. In turn, this may provide the framework for forecasting trends in the U.S. nuclear policy development regardless of the outcome of the 2020 elections. This paper examines nuclear policies of the George W. Bush, Barack Obama and Donald Trump administrations as set out in the Nuclear Posture Reviews (NPR) of 2002, 2010, and 2018 respectively and related strategic planning documents, as well as its manifestations in both strategic and non-strategic nuclear weapons development plans. The authors track the origins of the Donald Trump’s nuclear policy and demonstrate its continuity with the previous administrations’ strategies. The paper examines plans of large-scale modernization of all components of the U.S. nuclear triad outlined in the 2018 NPR. The authors assess the potential consequences of both the U.S. withdrawal from the Intermediate-Range Nuclear Forces Treaty and the non-renewal of the New START. The conclusion is drawn that with regard to Iran and North Korea the Trump administration’s policy will be largely similar to the policy of the G.W. Bush government but more assertive since the former considers nuclear weapons not only as a means of deterrence but as an efficient tool of military and political coercion. In its dealings with Russia and China the current administration might apply the so-called ‘Schlesinger Doctrine’, which might entail a return to the Cold War-era principles and strategies, though in a much more complex strategic environment. The authors warn of the risk of causing a recurrence of dramatic events similar to the 1962 and 1983 crises and express the hope that lessons drawn from the Cold War will pave the way for a new compromise.